2019 IEEE/CVF Conference on Computer Vision and Pattern Recognition (CVPR) 2019
DOI: 10.1109/cvpr.2019.01129
|View full text |Cite
|
Sign up to set email alerts
|

Unprocessing Images for Learned Raw Denoising

Abstract: Machine learning techniques work best when the data used for training resembles the data used for evaluation. This holds true for learned single-image denoising algorithms, which are applied to real raw camera sensor readings but, due to practical constraints, are often trained on synthetic image data. Though it is understood that generalizing from synthetic to real images requires careful consideration of the noise properties of camera sensors, the other aspects of an image processing pipeline (such as gain, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
348
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 383 publications
(348 citation statements)
references
References 45 publications
0
348
0
Order By: Relevance
“…(ii) Comparison with Deblock+GAN (Nos. 3,5,7). We found that the superiority of Deblock+GAN over standard GAN tends to be achieved as the quality Table 7.…”
Section: A13 Evaluation On Compression Robust Image Generation Undementioning
confidence: 85%
“…(ii) Comparison with Deblock+GAN (Nos. 3,5,7). We found that the superiority of Deblock+GAN over standard GAN tends to be achieved as the quality Table 7.…”
Section: A13 Evaluation On Compression Robust Image Generation Undementioning
confidence: 85%
“…The means of absolute errors (MAEs) between the predicted and true motion magnitudes were generated using the MPI-Sintel optical flow dataset (Butler et al 2012). The images were inverse-tone mapped into a simulated linear space using (Brooks et al 2019), and high-magnitude noise was added, with a standard deviation of 5% of the white level. The images were then downsampled to 256×192 using a triangle kernel before being processed by the algorithms.…”
Section: E Icient Motion Magnitude Estimationmentioning
confidence: 99%
“…After WB is applied to the raw-RGB image, a number of additional nonlinear photofinishing color manipulations are further applied by the ISP to render the final sRGB image [2]. These photo-finishing operations include, but are not limited to, hue/saturation manipulation, general color manipulation, and local/global tone mapping [8,27,33,44,47]. Cameras generally have multiple photo-finishing styles the user can select [2,33,34].…”
Section: Related Workmentioning
confidence: 99%